Targeted next-generation sequencing: the clinician’s stethoscope for genetic disorders - Haas, Jan; Sorici-Barb, Ioana; Katus, Hugo; Meder, Benjamin (Personalized medicine, 2014)
Genetic biomarkers are crucial for diagnosis, guiding of treatments and estimation of prognosis. In the past, clinical genetic diagnostics was limited by the sequencing information gained from selected exons and single genes. For genetically heterogeneous diseases, such as cardiomyopathies, where underlying mutations in more than 1000 exons are known, a Sanger-based comprehensive test would have been extremely expensive and labor intensive. Next-generation sequencing has overcome these problems in terms of costs, speed and throughput. In this review we discuss available methods for targeted next-generation sequencing that ease the introduction of this technology into routine clinical application. We further provide results of a study we have performed to compare two state-of-the-art methods for their enrichment efficiency and detection accuracy of variants in a clinical setting.